Direct Phosphination of Ferrocenium Ion with Tertiary Phosphines by the Mechanism of Oxidative Nucleophilic Substitution. Issue 40 (17th October 2018) - Chamkin, Aleksandr A.; Krivykh, Vasily V.; Nikitin, Oleg M.; Kreindlin, Arkady Z.; Shteltser, Nikolai A.; Dolgushin, Fedor M.; Artyushin, Oleg I.; Ikonnikov, Nikolai S.; Borisov, Yuri A.; Belousov, Yuri A.; Ustynyuk, Nikolai A.
Abstract : Ferrocenium salts [(C5 H5 )2 Fe]X (X = BF4, PF6 ) (I +· ) react with tertiary phosphines PR3 (PMe3, PEt3, P n Bu3, PMe2 Ph, and PMePh2 ) in dichloromethane at room temperature to form a mixture of the corresponding ferrocenylphosphonium salts [(C5 H5 )FeC5 H4 PR3 ]X (III ), ferrocene (I ), and phosphonium salts [HPR3 ]X. The same reaction was carried out in an electrochemical cell as the electrolysis of a solution of ferrocene and phosphine in dichloromethane at the oxidation potential of ferrocene. Possible reaction pathways for phosphination of ferrocenium ion were studied by DFT at the M06‐L/6‐311++G(d, p) theory level. The experimental and theoretical studies of this reaction suggest it to proceed according to the Scheme of oxidative nucleophilic substitution of hydrogen inI +· including the following steps: a) nucleophilic exo addition of a phosphine to the cyclopentadienyl ring ofI +· to form the radical cation adduct [(η 5 ‐C5 H5 )Fe · (η 4 ‐C5 H5 – + PR3 )]X (II +· ); b) redox reaction of the initial adductII +· with the starting ferrocenium saltI +· to result in ferrocene (C5 H5 )2 Fe (I ) and iron phosphoniocyclopentadiene dication [(η 5 ‐C5 H5 )Fe + (η 4 ‐C5 H5 – + PR3 )](X)2 (II 2+ ) where the Csp3 –H bond is involved in the agostic interaction with the metal atom; and c) deprotonation of the Csp3 –H bond inII 2+ by the starting phosphine to formIII . The relation between the data obtained and current concepts of C–H functionalization in transition metal arene and cyclopentadienyl complexes is discussed. Abstract : Ferrocenium saltsI +· react with tertiary phosphines to form a corresponding ferrocenylphosphonium saltsIII . Our studies suggest the Scheme of oxidative nucleophilic substitution: a) nucleophilic exo addition of a phosphine to the cyclopentadienyl ring ofI +· to form a radical cation adductII +· ; b) the redox reaction ofII +· withI +· to result in dicationII 2+ ; and c) deprotonation of the Csp3 –H bond inII 2+ to formIII .